Dynamic analysis of the boiler drum of a coal-fired thermal power plant. (November 2017) - Chandrasekharan, Sreepradha; Panda, Rames Chandra; Natrajan Swaminathan, Bhuvaneswari
The subcritical coal-fired boilers of thermal power plants consist of a combustion chamber, economizer unit, drum unit (drum, riser, and downcomer), superheater unit (primary superheater, secondary superheater, and final superheater), and reheater unit. The input and output of these units are highly interactive in nature. The efficiency of the subcritical plants is only around 33%. The efficiency needs to be increased to produce more power for the increasing demand, which can be achieved only by implementing supercritical technology or ultra-supercritical technology. However, the conversion of existing subcritical power plants to supercritical power plants is impossible due to the installation cost. So in order to increase the overall efficiency of the existing subcritical power plants, boilers of such units must be examined in order to find safer operational practices. This paper highlights the mathematical modeling of the economizer unit and drum unit of boiler, which can help in enhancing the performance of the boiler system of the power plant. Mass and energy balances for the integrating boiler units have been formulated using first principle laws. The developed model has then been validated with actual plant data obtained from a 210 MW coal-fired thermal power plant. The performance of the open loop responses of the model are analyzed and are included in the results and discussion of the paper. The model provides support for level, pressure, and temperature measurements and predictions. The effect of changes in the parameters of the boiler are studied and discussed in detail.